IN THE WAKE OF PUGACHEV’S REBELLION: EXPERIENCE IN ORAL HISTORY - N. V. Shevtsov (Vestnik MGIMO-Universiteta, 2016)
Grand uprising led by Pugachev seized a vast area from the middle reaches of the Volga, the Urals and the Kazakh steppes. Thousands of people from different classes and nationalities joined rebellious Ural Cossacks in 1773. From the beginning, the uprising was of antimonarchic, not noble character, although its leader, and posed as a resurrected Emperor Peter III. During two years since 1773 the rebels were holding at bay the entire Russian Empire, becoming a real threat to the power of Catherine II. Pugachev's Rebellion is a subject of numerous works of Russian historians, writers, articles, research journalists and ethnographers. But perhaps the most famous "History of Pugachev" is written by a classic of Russian literature Alexander Pushkin. His work became one of the first (if not the first) serious historical studies on Pugachev's Rebellion. The historical science of XIX century, especially its first half, doesn't know many writings on the uprising. The fact that historians did not dare to write about Pugachev and the events that took place in 1773-1775 years, as Catherine II prohibited even mention the uprising. The decree of the senate ordered even rename the place, where the described events took place, for example, the Yaik river and Yaitsk town in order "to bring all that has happened to eternal oblivion." The famous historian S.M. Solovyov did not have advance to write about Pugachev. Death interrupted his work when his 29 volume ws in process, which he planned to complete with the execution of the leader of the uprising. Russian historian V.O. Klyuchevskii did not write many pages devoted to Pugachev as well. The author of this article visited the places, where the events took place, and repeated the journey of A.S. Pushkin, who visited the region in 60years after Pugachev's Rebellion. By talking with the locals, visiting ancient towns and villages, I sought to find out what has now preserved since ancient times, whether it is possible today to see evidence of the uprising or the famous trip of A.S. Pushkin.